[OP.3D.07] CORRELATION OF CERULOPLASMIN WITH BIOMARKERS OF CARDIAC REMODELLING AND MYOFIBROSIS: NT-PROBNP, SST2, GALECTIN-3 IN PATIENTS WITH CHRONIC HEART FAILURE AND ARTERIAL HYPERTENSION. (September 2016) - MALEK, F.; Vondrakova, D.; Dvorak, J.; Sedlackova, L.; Andreasova, T.; Taborsky, L.; Neuzil, P.
Abstract : Objective: Ceruloplasmin is an acute phase protein with plasma copper binding properties. Several studies showed prognostic importance of ceruloplasmin in chronic heart failure. Study objective: to assess correlation of ceruloplasmin level with concentration of biomarkers of cardiac remodelling and myofibrosis in patients with chronic stable heart failure, and to compare that in subjects with arterial hypetension. Design and method: Blood samples were taken and serum levels of soluble ST2, galectin-3, NT-proBNP and ceruloplasmin were analysed in 164 consecutive patients with systolic HF from tertiary care heart failure clinic between 1st October 2014 and 31st May 2015. Mean patients[Combining Acute Accent] age was 65 years, mean LV EF was 32 %, ischemic aetilogy of CHF had 54 % patients. Control group comprised 64 patients with arterial hypertension (AH), with mean age 65 years, mean LV EF 68 % and no signs of heart failure. Results: Mean ceruloplasmin level in CHF group was 0.23 g/l and 0.20 in AH group (p < 0.001), mean galectin-3 level was 4156 ng/ml in CHF and 1470 in AH (p < 0.001), mean sST2 level was 233 ng/ml in CHF and 132 in AH (p = 0.23), and mean NT-proBNP was 218 pmol/l in CHF and 16.5 in AH (p < 0.001). Ceruloplasmin level correlated with NT-proBNP in CHF (r = 0.323, p < 0.001), but not with with sST2 and galectin-3. In AH group ceruloplasmin did not correlate significantly nor with NT-proBNP (r = 0.222, p = 0.08), neither with sST2 and galectin-3. In both groups together (n = 228), ceruloplasmin correlated significantly only with NT-proBNP (r = 0.349, p < 0.0001). Conclusions: Ceruloplasmin level in patients with stable CHS correlates with NT-proBNP concentration, but not with levels of other biomarker of cardiac remodelling. Mean ceruloplasmin level was significantly lower in patients with arterial hypertension compared to CHF subjects. The study was supported by internal grant Na Homolce Hospital, IG 140505.